3rd IEEE International Symposium on Biomedical Imaging: Macro to Nano, 2006.
DOI: 10.1109/isbi.2006.1624901
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automated Bioimage Analysis: From Features to Semantics

Abstract: Recent advances in bio-molecular imaging have afforded biologists a more thorough understanding of cellular functions in complex tissue structures. For example, high resolution fluorescence images of the retina reveal details about tissue restructuring during detachment experiments. Time sequence imagery of microtubules provides insight into subcellular dynamics in response to cancer treatment drugs. However, technological progress is accompanied by a rapid proliferation of image data. Traditional analysis met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In [11], methods are described to evaluate polymer transport and turnover in fluorescent speckle microscopy (FSM), based on cross correlation and particle flow. Approaches for tracking micro-tubules can be found in [50], where active contours and a hidden Markov model (HMM) are used [39], or in [14] for a speckle-based technique. A global minimization method by simulated annealing for the tracking of fluorescent structures was developed in [47].…”
Section: Bioimagingmentioning
confidence: 99%
“…In [11], methods are described to evaluate polymer transport and turnover in fluorescent speckle microscopy (FSM), based on cross correlation and particle flow. Approaches for tracking micro-tubules can be found in [50], where active contours and a hidden Markov model (HMM) are used [39], or in [14] for a speckle-based technique. A global minimization method by simulated annealing for the tracking of fluorescent structures was developed in [47].…”
Section: Bioimagingmentioning
confidence: 99%
“…Therefore, the development and evaluation of computerized algorithms that are specifically tailored for accurate and reproducible quantification of microscopic zebrafish images become an increasingly important necessity. While computerized analysis of bioimaging data has been extensively explored (Price et al 1998;Sjostrom et al 1999;Chen et al 2006;Shain et al 1999;Lin et al 2003;Yang and Parvin 2003;Loukas et al 2003;Byun et al 2006;Manjunath et al 2006;Parvin et al 2007), only a few studies of automated quantification for zebrafish images have been reported. Examples of such studies include the image processing system for scoring the schooling behavior of multiple zebrafish (Kato et al 2004), as well as the deformable model that was designed to segment and quantify the embryonic vasculature of zebrafish embryos from microangiography image series (Feng et al 2004).…”
Section: Introductionmentioning
confidence: 99%